The expression of Drosha, DGCR8, Dicer and Ago-2 genes are upregulated in human umbilical vein endothelial cells under hyperglycemic condition - Soufi Farhad Ghadiri (Sciendo, 2018)
Objectives. It has been shown that dysregulation of miRNAs expression contributes to the pathogenesis and progression of the diabetes and diabetes-related complications. Drosha, DGCR8, Dicer, and Ago-2 are involved in the miRNA maturation. The aim of the present study was to investigate the mRNA expression levels of these genes in the human umbilical vein endothelial cells (HUVECs) under hyperglycemic condition.